Youth Use of E-Cigarettes: Does Dependence Vary by Device Type? - Tackett, Alayna P. (Addict Behav, 2021)
INTRODUCTION: Youth nicotine dependence may vary by e-cigarette device used. METHODS: E-cigarette device type (“JUUL,” “similar pod/JUUL like device (i.e., pod mod),” or “other type of e-cigarette” (i.e., tank, mod)), nicotine dependence (Hooked on Nicotine Checklist; HONC), frequency of e-cigarette use (i.e., weekly, daily, monthly), and covariates were examined via a convenience sample of youth who use e-cigarettes in the United States via an online Qualtrics panel survey from April 2019 to May 2019. RESULTS: Youth aged 13–17 (Mean age = 15.9 years, SD = 1.0 year; n=185) were mostly 72.4% female. Primary device used by category was endorsed as follows: JUUL n = 87, pod mod n = 42, and other type of e-cigarette n = 56. Participants endorsed an average of 4.5 / 10 HONC symptoms (SD=3.6). Compared to other e-cigarettes, youth who used JUUL and pod mod devices endorsed more dependence symptoms, even when adjusting for current smoking status (JUUL IRR = 1.96, 95% CI 1.30–2.97; pod mod device IRR = 1.76, 95% CI 1.08–2.87). In total, HONC symptoms significantly differed by device for 8/10 symptoms, with JUUL and pod mod users reporting higher frequency of items compared to other e-cigarette devices. CONCLUSIONS: Features of nicotine dependence experienced by youth (i.e., feeling a stronger urge to vape) differed by primary device used, with those using JUUL and pod-mods reporting a greater level of dependence. Regulation of features of e-cigarette devices that may increase nicotine delivery and subsequent development of dependence among youth warrant urgent consideration.